2013
DOI: 10.1007/s00062-013-0222-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Appearance of Primary Spinal Extradural Ewing’s Sarcoma: Case Report and Literature Review

Abstract: The MR imaging appearance of PSEESs is indistinguishable from other tumors. PSEES should be assumed as the differential diagnosis of spinal extradural tumors in pediatric, adolescent, and young adult patients, and prompt surgical exploration should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Case 12 in our series is the sixth male and seventh patient in this category, and the patient is currently in good condition now. The radiographic findings of primary spinal pPNETs are usually not helpful in diagnosis and differential diagnosis, as was stated by previous studies [15,19]. Radiological diagnosis may be neurinoma, meningioma, neurofibroma, especially neurinoma.…”
Section: Radiological Featuresmentioning
confidence: 90%
See 2 more Smart Citations
“…Case 12 in our series is the sixth male and seventh patient in this category, and the patient is currently in good condition now. The radiographic findings of primary spinal pPNETs are usually not helpful in diagnosis and differential diagnosis, as was stated by previous studies [15,19]. Radiological diagnosis may be neurinoma, meningioma, neurofibroma, especially neurinoma.…”
Section: Radiological Featuresmentioning
confidence: 90%
“…Their study showed that there was often minimal contrast enhancement [15]. Tsutsumi et al [19] reviewed the literature and found that varying enhancement was noted. Moderate to prominent contrast enhancement were found in most of our cases.…”
Section: Radiological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Most common site of occurrence is thoracic followed by cervical and lumbar spines. 43 The main clinical presentation is back pain, but up to 60% of patients have neurological defi cit. MRI is the diagnostic imaging study of choice.…”
Section: Primary Malignant Extradural Spinal Tumors Ewing's Sarcomamentioning
confidence: 99%
“…MRI is the diagnostic imaging study of choice. 43 Best treatment is aggressive surgical resection followed by radiation and chemotherapy. 27,40 The local control approaches 100% and long term survival is 86%.…”
Section: Primary Malignant Extradural Spinal Tumors Ewing's Sarcomamentioning
confidence: 99%